Working Capital Management, Free Cash Flow, Profitability And Firm Value - Aurora Angela; Vinny Stephanie Hidayat; Eiren Eunike (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
The main goal of a company is to optimize the firm’s value. A good working capital management, free cash flow, and profitability are expected to increase the firm’s value. This study analyzes on how working capital management, free cash flow, profitability, and firm value relate. This study uses the population of all food and beverage sub-sector companies in Indonesia from the period of 2019 - 2021. The technique used to test the hypothesis is multiple linear regression analysis. The results of the study are, that working capital management, free cash flow, and profitability have an effect towards firm value. Therefore, companies must pay attention to their cash conversion cycle, have a positive free cash flow so that there is flexibility in the company's finances, also in increasing profits so that ROA becomes higher hence investors will respond to this positive signal and the firm value will increase.